The effect of chitin on the effectiveness of Beauveria bassiana formulation product to control cocoa pod borer in vitro - Eka Nurhangga; Winda Nawfetrias; Nailulkamal Djamas; Akhmad Jufri (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2024)
Fungal entomopathogens are suggested to be used as a bioinsecticide due to their biological persistence and ecological friendliness. Beauveria bassiana is an entomopathogenic fungus that can effectively control insect pests, including cocoa pod borer. This study aims to determine the level of effectivity of the B. bassiana (Bb) formulation product from Palu against cocoa pod borer pupae in vitro . This research used a completely randomized design (CRD) consisting of two factors: conidia concentrations and chitin treatments, which were repeated thrice. The conidia concentrations consisted of two levels, that were 106 and 107 conidia/mL. The chitin treatment included seven treatments: isolate from Kediri without formulation with chitin (Bb-K), isolate from Palu without formulation with chitin (Bb-P0), four formulations of isolates from Palu with the addition of chitin to various growth media (Bb-P1, Bb-P2, Bb-P3, and Bb-P4), and control (without Bb suspension). Bb-P0 and Bb-P2 treatments at a concentration of 107conidia/mL began to colonize CPB on the third day after the treatment application, while the other formulations started on the fifth day. However, Bb-P0 showed the lowest infection rate at the end of the observation. Contrarily, the data on the pupa-infected ratio showed that the Bb-P2 treatment was the highest compared to other treatments. It conformed to the adult emergence ratio that Bb-P2 exhibited the lowest, which means Bb-P2 has the most virulence of other formula. The result showed that PDA and PDB media-supplemented chitin was the most effective for culturing B. bassiana origin Palu before mass production.